Phase II Study of Preoperative Treatment with External Radiotherapy Plus Panitumumab in Low‐Risk, Locally Advanced Rectal Cancer (RaP Study/STAR‐03). (9th March 2018) - Pinto, Carmine; Di Bisceglie, Maurizio; Di Fabio, Francesca; Bochicchio, Annamaria; Latiano, Tiziana; Cordio, Stefano; Rosati, Gerardo; Aschele, Carlo; Marino, Antonella; Bergamo, Francesca; Bustreo, Sara; Frassineti, Luca; et al.
Abstract : Background: Treatment with fluoropyrimidines and concomitant long‐course external radiotherapy (RTE) is the standard of care in locally advanced rectal cancer (LARC) preoperative chemoradiation. A randomized phase II study (RaP/STAR‐03) was conducted that aimed to evaluate the activity and safety of the monoclonal antibody anti‐epidermal growth factor receptor panitumumab as a single agent in combination with radiotherapy in low‐risk LARC preoperative treatment. Materials and Methods: Patients had adenocarcinoma of the mid‐low rectum, cT3N− or cT2–T3N+, KRAS wild‐type status, and negative circumferential radial margin. Panitumumab was administered concomitant to RTE. Rectal surgery was performed 6–8 weeks after the end of preoperative treatment. The adjuvant chemotherapy regimen was FOLFOX. The primary endpoint was the pathologic complete response (pCR) rate. The sample size was calculated using Simon's two‐stage design. A pCR of 16% was considered to qualify the experimental treatment for further testing. Results: Ninety‐eight patients were enrolled in 13 Italian centers from October 2012 to October 2015. Three panitumumab infusions were administered in 92 (93.4%) patients. The RTE compliance was median dose 50.4 Gy; ≥28 fractions in 82 (83.7%) patients. Surgical treatment was performed in 92 (93.9%) patients, and no severe intraoperative complications were observed. A pCR was observed in 10 (10.9%) patients (95% confidence interval, 4.72%–17.07%). Pathological downstaging occurred in 45 (45.9%) patients. Grade 3 toxicities were observed in 22 (22.3%) patients, and the common adverse events were skin rash in 16 (16.3%) patients. No grade 4 toxicities were reported. Conclusion: The pCR rate (our primary endpoint), at only 10.9%, did not reach the specified level considered suitable for further testing. However, the analysis showed a good toxicity profile and compliance to concomitant administration of panitumumab and RTE in preoperative treatment of LARC. The pCR evaluation in all wild‐type RAS is ongoing. Implications for Practice: The aim of the RaP/STAR‐03 study was to evaluate the activity and safety of monoclonal antibody anti‐epidermal growth factor receptor (EGFR) panitumumab as a single agent without chemotherapy in low‐risk, locally advanced rectal cancer (LARC) preoperative treatment. Nevertheless, the use of panitumumab in combination with radiotherapy in preoperative treatment in patients with KRAS wild type and low‐risk LARC did not reach the pathologic complete response primary endpoint. This study showed a good toxicity profile and compliance to combination treatment. Further analysis of NRAS and BRAF on tissue and circulating levels of the EGFR ligands and vascular factors (soluble vascular endothelial growth factor, E‐selectin) may provide insight on the potential molecular pathways involved in the anti‐EGFR response. Abstract : This study evaluated the activity and safety of monoclonal antibody anti‐EGFR panitumumab single agent without chemotherapy in low‐risk LARC preoperative treatment. The use of anti‐EGFR monoclonal antibodies in combination with radiotherapy in preoperative treatment in patients with KRAS wild type and low‐risk LARC did not reach the pCR primary endpoint; however, this study showed a good toxicity profile and compliance to combination treatment.